The Effect of Immigration on Native Earnings - Aslan Zorlu; Joop Hartog (Tinbergen Institute, 2000)
This study investigates the extent of labour market competition among nativeDutch workers and ethnicminorities, using national survey of the SEO and the Population statistics ofthe CBS. Firstly, the directeffect of immigrants on local labour markets is considered. It is shown thatethnic minorities fromdeveloping countries have a positive effect on the earnings of high skillednatives and an adverse effect onthe earning of low skilled native workers. On the other hand, ethnic minoritiesfrom EU-countries may havea negative effect on the earnings of high skilled natives and a positive effecton the earnings of low skillednatives. Secondly, the effect of an immigration flow by 5% of the total labourforce on native earnings isexamined along three scenarios using a general equilibrium model. It is foundthat immigration has a largenegative effect on the wages of less skilled natives and a small positive effecton the wages of high skilledworkers as new immigrants are less skilled than natives. In the case thatimmigration flow is mainlycomposed of high skilled workers, immigration has a relative large adverseeffect on high skilled natives anda small negative effect on low skilled natives. In all cases, medium skillednatives are a little adverselyaffected by immigrants.
Keywords: F22; J15; J23; 330; immigrants; wages; Lohn; Lohnstruktur; Einwanderung; Berufsbildung; Niederlande